Duplication Cyst with Intestinal Volvulus Causing Intestinal Atresia/Stenosis in Neonates - Bilal Mirza; Imran Hashim; Shabbir Ahmad; Nabila Talat; M Zubair Shaukat; Muhammad Saleem (EL-Med-Pub, 2018)
Duplication cysts of small bowel seldom present in newborns and usually represent the development of complications. In utero complications may lead to mesenteric vascular accidents and thus resulting in intestinal atresias. We report three neonates with duplication cyst of small bowel causing localized intestinal volvulus, leading to small bowel intestinal atresia/stenosis. The neonates underwent excision of the duplication cyst and resection anastomosis of the small bowel. Post-operative recovery was uneventful in all three of them.